1969
DOI: 10.1128/am.17.2.268-274.1969
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Persistence of Staphylococcus aureus on Fabrics

Abstract: The persistence of Staphylococcus aureus (Smith) on wool blanket, wool gabardine, cotton sheeting, cotton knit jersey, cotton terry cloth, and cotton wash-and-wear fabrics was studied. The fabrics were exposed to bacterial populations by three methods: direct contact, aerosol, and a lyophilized mixture of bacteria and dust having a high content of textile fibers. The contaminated fabrics were held in 35 or 78% relative humidities at 25 C. In general, the persistence time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 11 publications
0
9
1
Order By: Relevance
“…No difference for any culture media between the two R.H. environments was found. Again, this is in contrast with findings from Wilkoff et al [31], where Staphylococcus aureus survived for longer at 35 % R.H. compared to 78 % R.H., although our smaller humidity range may account for the difference in results. Wilkoff et al [31] examined the survival of only one strain of bacteria, whereas we investigated a range of bacteria, which may have exhibited a greater tolerance to changes in R.H and S. aureus may not have been present at all.…”
Section: Effect Of Relative Humidity On Bacterial Growthcontrasting
confidence: 99%
“…No difference for any culture media between the two R.H. environments was found. Again, this is in contrast with findings from Wilkoff et al [31], where Staphylococcus aureus survived for longer at 35 % R.H. compared to 78 % R.H., although our smaller humidity range may account for the difference in results. Wilkoff et al [31] examined the survival of only one strain of bacteria, whereas we investigated a range of bacteria, which may have exhibited a greater tolerance to changes in R.H and S. aureus may not have been present at all.…”
Section: Effect Of Relative Humidity On Bacterial Growthcontrasting
confidence: 99%
“…Until now, two basic types of textile sampling methods, which vary depending on the state fabric at the end of the process, have been described: Nondestructive methods, in which the test fabric remains essentially unaltered after sampling: impression sampling, specifically RODAC or contact plating, 19 release of fabric-bound dust and cellular particles onto sterile sampling surfaces by scraping with an inverted petri dish (sweep plating), 20 sampling by means of nutrient agar sausages, 21 sampling by impact upon the fabric surface (percussion sampling), 22 the use of a Folin bubbler apparatus with attached funnel. 23,24 Destructive methods, in which the test fabric is rendered unsuitable for use after completion of the sampling process: maceration 23,25,26 of fabric samples in a defined liquid medium, agitation 13,2729 of fabric samples in a defined liquid medium, overlaying fabric samples with agar. 27,30 …”
Section: Introductionmentioning
confidence: 99%
“…Destructive methods, in which the test fabric is rendered unsuitable for use after completion of the sampling process: maceration 23,25,26 of fabric samples in a defined liquid medium, agitation 13,2729 of fabric samples in a defined liquid medium, overlaying fabric samples with agar. 27,30 …”
Section: Introductionmentioning
confidence: 99%
“…No laboratory experiment that investigated fabrics demonstrated that the type of polymer affects the survival of bacteria because experimental treatments varied by both type of polymer and fabric construction (i.e., drapes, keyboard covers, towels). , Despite this, they do provide some evidence that sunlight and temperature can affect the survival of bacteria. , Colclasure et al (2015) concluded that coliform bacteria survive at greater rates in cooler shaded areas and Wilkoff et al (1969) concluded that more S. aureus survive in cooler temperatures …”
Section: Survivalmentioning
confidence: 99%